2004
DOI: 10.1128/jb.186.5.1374-1380.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for HrpXo-Dependent Expression of Type II Secretory Proteins in Xanthomonas oryzae pv. oryzae

Abstract: Xanthomonas oryzae pv. oryzae is a causal agent of bacterial leaf blight of rice. Recently, an efficient hrp-inducing medium, XOM2, was established for this bacterium. In this medium, more than 10 proteins were secreted from the wild-type strain of X. oryzae pv. oryzae. Many of these proteins disappeared or decreased in amount in culture on XOM2 when incubated with the strain that has a mutation in the hrp regulatory gene. Interestingly, the secretory protein profile of a mutant lacking a type III secretion sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 40 publications
5
55
1
3
Order By: Relevance
“…Multiple export pathways in various bacteria have been established, including a type III (114,285,310), a type IV (82), and the twin-arginine translocation (Tat) (81) pathways. However, there are still proteins, including those mentioned above, that are secreted by an unidentified route(s) and lack anchorage structures in the bacterial cell wall (21, 57).…”
Section: Reaching the Cell Surfacementioning
confidence: 99%
“…Multiple export pathways in various bacteria have been established, including a type III (114,285,310), a type IV (82), and the twin-arginine translocation (Tat) (81) pathways. However, there are still proteins, including those mentioned above, that are secreted by an unidentified route(s) and lack anchorage structures in the bacterial cell wall (21, 57).…”
Section: Reaching the Cell Surfacementioning
confidence: 99%
“…citri [29] and extracellular proteases in Xcc [21]. In Xoo, only a gene encoding the extracellular T2SS enzyme Cysp2, which is related to pathogenicity, has so far been demonstrated to be regulated by HrpX [19]. These reports support that HrpX is also involved in regulating the expression of some T2SS-related extracellular enzymes.…”
Section: Discussionmentioning
confidence: 82%
“…Yamazaki et al (2008) have suggested the presence of an imperfect PIP box for the CPXAC gene. By contrast, pathogenicity genes hrpX and hrpG are responsible for the secretion of proteins in type III and some type II systems (Sandkvist, 2001;Furutani et al, 2004). Furthermore, a functional interplay between both secretion systems has been suggested (Büttner and Bonas, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This high degree of similarity was expected, as both organisms belong to the family Xanthomonadaceae. The sequence of cysteine peptidase from Xac is also similar to that of Pseudomonas syringae (76% similarity), which causes leaf spot disease on tomato plants (Hirano and Upper, 2000); a cysteine peptidase from the bacterium Xylella fastidiosa (72% similarity), which is responsible for citrus variegated chlorosis ; and to a cysteine peptidase from X. oryzae (70% similarity), which is the causal agent of bacterial leaf blight in rice (Furutani et al, 2004). With the exception of the sequence from X. fastidiosa, which has been studied by Nogaroto et al (2006), the translation initiation sites of all sequences used in the alignment of Figure 1 were verified only with genome annotation.…”
Section: In Silico Analysis Of Cysteine Peptidase (Open Reading Framementioning
confidence: 94%